A Label-Free Electrochemical Immunosensor Based on AuAgPt NDs Functionalized MoO2 Nanosheets for Highly Sensitive Detection of AFP. Issue 5 (5th May 2021) - Yang, Qingshan; Wang, Ping; Tang, Feng; Wang, Shujun; Zhao, Zhe; Wang, Yao; Li, Yueyun; Liu, Qing; Dong, Yunhui
Abstract : In this work, a label-free electrochemical immunosensor was structured for detecting alpha fetal protein (AFP) effectively. The proposed electrochemical immunosensor was structured by gold silver platinum nanodendrites loaded on amino-functionalized MoO2 nanosheets (AuAgPt NDs/NH2 -MoO2 NSs). The AuAgPt NDs with rich dendrite structure provided abundant specific surface area for effective capture antibody. MoO2 possessed the satisfactory catalytic ability in terms of H2 O2 reduction and charge transfer capacity. AuAgPt NDs possessed favourable catalytic performance to H2 O2 reduction. Therefore, the prepared AuAgPt NDs/NH2 -MoO2 NSs was better than AuAgPt NDs and NH2 -MoO2 NSs in H2 O2 reduction on account of a synergistic effect. The constructed electrochemical immunosensor possessed a satisfying detection limit of 3.3 fg ml −1 and a broad detection range which was from 10 fg ml −1 to 100 ng ml −1 (S/N = 3) for the AFP detection under optimal conditions. The constructed electrochemical immunosensor possessed favourable detection performance in sensitivity, stability, selectivity and reproducibility, which indicated that it possessed a practical application in the aspect of clinical detection.